Tributação indutora e o desenvolvimento sustentável quanto às fontes de energia renováveis - Monteiro, Wellington de Serpa (2020)
This dissertation analyzes the possibility of tax induction in promoting sustainable development in the renewable energies sector. An interdisciplinary perspective is undertaken involvin Law and Economy. It analyze the idea of development and the evolution of it, demonstrating the expansion of its scope in an understanding that covers both the social aspect and sustainability, and which will have repercussions in the Federal Constitution of 1988, giving our current state a socio-environmental State character, in a systematic way, it should seek sustainable development. To this objetive, creat its Fiscal State, necessary to obtain the economic means to achieve the constitutional objectives, which must necessarily observe the tax parameters provided for in our Political Charter and which can be used, depending on its principles, in addition to the purely collecting purposes, to induce conducts that favor a sustainable development of character, notably in the area of energy, since it is essential to development and plays a major role in the generation ecological problems (pollution), depending on or without their sources being clean and renewable. In the Brazilian case, the innovative nature and wide growth possibilities of solar, biomass and wind. In the question relevant to the procedures, descriptive methodologies will be used. The methodological procedures to be used in the proposed research were the bibliographic research on the following topics related to the object of study: sustainable development, inductive taxation, national energy and electrical matrix, renewable energy sources, among others. The research is conclusive in the sense of the need for efficiency of extrafiscality in the field of energy, which will occur as long as it observes its national role as inducer of conducts that favor not only the necessary expansion of electricity generation, but generation of energy from renewable sources and with minimal environmental costs. It is concluded by the feasibility of using tax induction in promoting sustainable development in the area of renewable energy.